1980
DOI: 10.1159/000468420
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Withdrawal Syndrome: Treatment with Trazodone

Abstract: Central monoaminergic pathways dysfunction has been shown in the alcohol withdrawal syndrome of experimental animals: noradrenergic hyperfunction and serotonin transmission impairment is suggested by many studies. Trazodone is a new psychotropic drug which has a marked norepinephrine receptor blocking power; moreover, it inhibits serotonin reuptake and was fully effective in the treatment of man's withdrawal syndrome (17 alcoholic inpatients). The good therapeutical results make it conceivable that monoaminerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Although many reports suggest that abnormalities occur in a number of central and peripheral neurotransmitter systems during the alcohol withdrawal period (Ahtee and Svartstrom‐Fraser, 1975; Glue and Nutt, 1990; Hawley et al., 1985; Potter et al., 1984; Roccatagliata et al., 1980; Smith et al., 1990), the mechanisms of the pathophysiology of ethanol withdrawal signs, and of cardiovascular changes in particular, are complex and poorly understood. The rates of total norepinephrine spillover into plasma are increased in patients with ventricular arrhythmia (Meredith et al., 1991), the sympathovagal imbalance in HRV is related to left ventricular systolic function both in cases of in‐hospital heart failure and with progressive left ventricular dilatation after myocardial infarction (Kleiger et al., 1987; Odemuyiwa et al., 1994), and the sympathetic nervous system activation related to the incidence of ventricular ectopy in ischemic heart disease (Anonymous, 1995; Bertel et al., 1982; Lombardi et al., 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Although many reports suggest that abnormalities occur in a number of central and peripheral neurotransmitter systems during the alcohol withdrawal period (Ahtee and Svartstrom‐Fraser, 1975; Glue and Nutt, 1990; Hawley et al., 1985; Potter et al., 1984; Roccatagliata et al., 1980; Smith et al., 1990), the mechanisms of the pathophysiology of ethanol withdrawal signs, and of cardiovascular changes in particular, are complex and poorly understood. The rates of total norepinephrine spillover into plasma are increased in patients with ventricular arrhythmia (Meredith et al., 1991), the sympathovagal imbalance in HRV is related to left ventricular systolic function both in cases of in‐hospital heart failure and with progressive left ventricular dilatation after myocardial infarction (Kleiger et al., 1987; Odemuyiwa et al., 1994), and the sympathetic nervous system activation related to the incidence of ventricular ectopy in ischemic heart disease (Anonymous, 1995; Bertel et al., 1982; Lombardi et al., 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly obscure is the reason for the exacerbation of drinking severity upon stoppage of trazodone but not placebo. One prior study suggested that trazodone can alleviate symptoms of alcohol withdrawal (Roccatagliata et al, 1980) Although causal direction is uncertain, one can speculate that post-acute alcohol withdrawal symptoms including sleep disturbance, reemerged with cessation of trazodone and triggered alcohol consumption. Concern about the cessation of trazodone leading to more drinking is salient because research and clinical experience suggest that medication adherence is problematic in alcohol-dependent populations (Swift, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Trazodone, a second generation antidepressant with sedative properties, has been shown to be effective in alcohol withdrawal treatment more than twenty five years ago [5], but few subsequent studies have been conducted. Moreover, these studies dealt with lasting post-withdrawal symptoms such as sustained alcohol craving, depression and insomnia [4].…”
Section: Introductionmentioning
confidence: 99%